becoming-guitar: a childlike challenge (to philosophy and education) - barreira vicente santos, fulvio; miranda de paiva, jair (childhood & philosophy, 2024)
This article seeks to reflect a journey of awareness experienced by a teacher who discovers the destabilizing and inspiring force of children’s childhood, during philosophy classes. When investigating the (im)possibility of children doing philosophy, we see similarities with the experience of playing the guitar, in which there is a conceptual character that helps us (re)think about teaching philosophy to children. In this text, we rehearse ways of exploring the meanings that emerge from experiences lived between childhood and philosophy based on encounters in classrooms, to find/create possibilities to fuel this investigation instead of putting an end to it. An exercise that allows us to find/build more welcoming, sensitive and inventive ways of doing, living and inhabiting education between childhood and philosophy at school. We thus come across the idea (body-concept) of becoming-guitar, which we work on based on meetings with Gilles Deleuze and Jean-Luc Nancy. Life. That’s what this text and research is about; because when it comes to education, these two things are connected, they happen together, they share paths, they are inseparable, in the same way that we cannot separate the sound from the goosebumps they cause on our skin. The text is, first of all, an invitation to listen to what moves us, not to explain or substantiate our practices, but to discover and invent meanings: being in-with-others, between education, philosophy, childhoods and schools.